PERAN SUTRADARA DAN KAMERAMAN DALAM FILM DOKUMENTER "COURIER: LIFE CHANGING" - Azis Ahmad Taqiyuddin (2023)
The documentary film entitled Courier: Life Changing is a film that documents the career journey of three couriers who have different backgrounds to become bicycle couriers. This film also tries to show the bicycle courier business that was formed from a community to become a partnership company in the city of Jakarta which has existed since 2014 and has managed to survive and continue to grow until now. This film tries to give a view to the public that a job and business that starts from a hobby and community can change a person's destiny. Keywords: Documentary Film, Bicycle Courier